(untitled) (Revista revoluciones, 2022)
From subaltern studies, Spivak tells us that subaltern groups do not have enunciative authority. This lack of enunciative authority is due to the existence of unequal social and cultural positions, where only the voice of the one who presents himself as the dominator exists, even if he claims to speak for others. If we consider Spivak’s answer to be correct, then why can’t the subaltern speak? This is where the proposal from Latin American decolonial thought and Quijano’s idea of the coloniality of power becomes interesting. The fact that the subaltern does not possess enunciative authority means that there has been a process that has made them invisible in order to keep them in silence, which is false, since subaltern groups, as subaltern studies have announced, do possess their own spaces, their own voices, their own ways of doing things that the dominated cannot and do not wish to hear or see. Quijano’s coloniality of power explains to us, from a general context, what has happened to feel this false silence.